What information did the DSM-5 Cultural Formulation Interviews provide when used with Swedish-speaking patients in a psychiatric setting in Stockholm? - Wallin, Malin Idar; DeMarinis, Valerie; Nevonen, Lauri; Bäärnhielm, Sofie (Frontiers in Psychiatry, 2024)
Introduction Cultural and contextual factors affect communication and how psychiatric symptoms are presented, therefore psychiatric assessments need to include awareness of the patients’ culture and context. The Cultural Formulation Interview (CFI) in DSM-5 is a person-centred tool developed to support the exploration of cultural and contextual factors in an individualized and non-stereotypic way. Methods The aim of this qualitative study was to find out what information the DSM-5 CFI revealed when used with native Swedish-speaking patients as part of routine clinical psychiatric assessment at an outpatient clinic. An additional aim was to enhance understanding of what kind of information the questions about background and identity yielded. The CFI was added to the psychiatric assessment of 62 native Swedish-speaking patients at an outpatient psychiatric clinic in Stockholm. Results From the thematic analysis of the documented CFI answers, six central themes were found; Descriptions of distress and dysfunction, Managing problems and distress, Current life conditions affecting the person, Perceived failure in meeting social expectations, Making sense of the problem, and Experiences of, and wishes for, help. The CFI questions about identity yielded much information, mainly related to social position and feelings of social failure. Discussion For further refinement of the CFI, we see a need for re-framing the questions about cultural identity and its impact on health so that they are better understood. This is needed for majority population patients as direct questions about culture may be difficult to understand when cultural norms are implicit and often unexamined. For clinical implications, our findings suggest that for cultural majority patients the DSM-5 CFI can be a useful person-centred tool for exploring cultural and, in particular, social factors and patients’ perception and understanding of distress.